Next‐generation sequencing in salivary gland carcinoma: Targetable alterations lead to a therapeutic advantage—Multicenter experience. Issue 4 (24th November 2019) - Moore, Assaf; Bar, Yael; Maurice‐Dror, Corinne; Ospovat, Inna; Sarfaty, Michal; Korzets, Yasmin; Goldvaser, Hadar; Gordon, Noa; Billan, Salem; Gutfeld, Orit; Popovtzer, Aron
Abstract: Background: Salivary gland cancers (SGCs) are rare. The approach to metastatic patients is histology‐dependent. There is little evidence on whether next‐generation sequencing (NGS) findings translate to tumor control in SGCs. Methods: We analyzed all patients with histologically confirmed SGC who underwent NGS. Results: Twenty‐seven patients were identified, 14 (51.8%) had targetable findings in NGS: 5 ERBB2 amplifications, 3 PIK3CA mutations, 2 RUNX1 mutations, 1 TRIM33‐RET fusion, 1 FGFR3‐TACC3 fusion, 1 microsatellite instability‐high, and 2 high mutational burden. Ten patients were treated accordingly. Median progression‐free survival for targeted treatment was 8.4 months. Of five patients who achieved durable responses of 8.4 to 31.3 months, two are ongoing. The overall median survival was not reached for patients receiving targeted treatment and was 40.4 months for patients treated conventionally ( P = .18). Conclusions: In the absence of a well‐established therapeutic approach, NGS may detect clinically significant genetic alterations and benefit patients with advanced SGC.